Pengaruh Latihan Sirkuit Terhadap Biomarker Inflamasi,Kapasitas Fungsional, Fungsi Paru, dan Kualitas Hidup Pasien Gagal Jantung Kronik - Fauzan Muttaqien; Yulvina Yulvina; Riana Novita Sari; Fahmi Syarif; Sri Wahyudati; Sefri Noventi Sofia; Sodiqur Rifqi (Medica Hospitalia : Journal of Clinical Medicine, 2019)
Background: Physical exercise in patients with heart failure maydecrease the level of proinflammatory biomarkers,increase maximal oxygen consumption, improve pulmonary function and quality of life. Circuit training is one of the most advantageous exercise models because it improves cardiorespiratory fitness and muscle strength. Objective: This study was aimed to investigate the effect of circuit training on proinflammatory biomarkers, functional capacity, pulmonary function, and quality of life in patients with chronic heart failure in RSUP Dr. Kariadi Methods: Twenty-six stable chronic heart failure with reduced ejection fraction patients were randomized into exercise group that received circuit training in the rehabilitation center of Kariadi Hospital for a month and control group. TNF- ? levels, maximum oxygen consumption, pulmonary function, and quality of life were taken before and after the exercise period. Data between two groups was analyzed with the Mann-Whitney test. Pre and post data was analyzed with the Wilcoxon test. Results: Nine-teensubjects completed the study without any significant side effects.There was no significant difference in TNF-? levels before and after treatment between treatment groups and control groups (p=0,513). The treatment group with circuit training showed a greater increase in maximum oxygen consumption (p=0,034), greater increase in Forced Vital Capacity value(p=0,010) and a greater increase in quality of life score(p=0,047)than the control group. Conclusion: Circuit training in patients with chronic heart failure can increase maximal oxygen consumption, lung function, and quality of life, but no changes in inflammatory biomarkers. Keywords: Circuit training, TNF-a, maximal oxygen consumption, FVC, quality of life Latar belakang: Latihan fisik pada pasien gagal jantung dapat menurunkan kadar biomarker proinflamasi, meningkatkan konsumsi oksigen maksimal, memperbaiki fungsi paru dan meningkatkan kualitas hidup. Latihan sirkuit merupakan salah satu model latihan fisik yang lebih menguntungkan karena mampu memperbaiki kebugaran kardiorespirasi dan kekuatan otot sekaligus. Tujuan:Menganalisispengaruh latihan sirkuit terhadap biomarker inflamasi, kapasitas fungsional, fungsi parudan kualitas hiduppasien gagal jantung kronik di RSUP Dr.Kariadi. Metode:Dua puluh enam pasien gagal jantung kronik stabil dengan penurunan fraksi ejeksi ventrikel kiri dirandomisasi menjadi kelompok yang mendapatkan latihan sirkuit di bagian rehabilitasi RSUP Kariadi selama 1 bulan dan kelompok kontrol. Kadar TNF-a, nilai konsumsi oksigen maksimal, fungsi paru, dan kualitas hidupdiambil sebelum dan sesudah periode latihan. Analisis data antara dua kelompok menggunakan uji Mann-Whitney.Analisis data pre dan post, menggunakan uji Wilcoxon Hasil: Sembilan belas subjek menyelesaikan studi tanpa ada efek samping.Tidak didapati perubahan kadar TNF-a sesudah latihan sirkuit (p=0,513);Kelompok perlakuan dengan latihan sirkuit menunjukkan peningkatan konsumsi oksigen maksimal yang lebih besar (p=0,034), rerata peningkatan nilai FVC (Forced Vital Capacity) setelah latihan yang lebih besar (p=0,010), sertarerata peningkatan kualitas hidup yang lebih besar (p=0,047) dibandingkan kelompok kontrol. Simpulan: Latihan sirkuit pada pasien gagal jantung kronik dapat meningkatkan konsumsi oksigen maksimal, fungsi paru, dan kualitas hidup, namun tidak menyebabkan perubahan padabiomarker inflamasi. Kata Kunci: Latihan sirkuit, TNF-a, konsumsi oksigen maksimal, FVC, kualitas hidup